RETRACTED: How Government Corruption and Market Segmentation Affect Green Total Factor Energy Efficiency in the Post-COVID-19 Era: Evidence From China - Zhou, Qingjie; Du, Mingyue; Ren, Siyu (Frontiers in Energy Research, 2022)
Energy and environmental pollution have attracted widely attention, but few studies have been conducted on green total factor energy efficiency (GTFEE) from the perspective of government corruption and market segmentation. By using the panel data of 30 provinces in China for the period 2006 to 2017, this study tests the relationship between government corruption, market segmentation and GTFEE. Moreover, considering the threshold effect of government corruption and market segmentation on GTFEE, the system generalized method of moments and the dynamic threshold panel model are adopted to analyze the nonlinear relationship. The regression results indicate that government corruption significantly decrease GTFEE, and market segmentation also has a significant negative impact on GTFEE. Moreover, market segmentation exacerbates the negative impact of corruption on GTFEE. The more serious the government corruption, the more severe the inhibitory effect of market segmentation on GTFEE. Similarly, the higher degree of market segmentation can increase the restraining effect of corruption on GTFEE. The study results are still valid after the robustness tests. In view of the conclusion, this paper proposes some policies recommendation to increase the GTFEE, which can be used for reference by other countries.